2003
DOI: 10.1096/fj.02-1024fje
|View full text |Cite
|
Sign up to set email alerts
|

l‐Carnitine: a nutritional modulator of glucocorticoid receptor functions

Abstract: L-carnitine is an essential nutrient with a major role in cellular energy production. There is evidence that, at high doses, L-carnitine might mimic some of the biological activities of glucocorticoids, especially immunomodulation. To explore the molecular basis of this effect, we tested the influence of L-carnitine on glucocorticoid receptor-alpha (GRalpha) functions. Millimolar concentrations of L-carnitine, which were not cytotoxic in vitro, significantly reduced the whole cell binding of [3H]dexamethasone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 44 publications
3
34
1
Order By: Relevance
“…As evidenced in the present study, MTX administration resulted in increased serum TNF-α, indicating the role of this cytokine in drug-induced toxicity, while L-carnitine depressed the TNF-α response. Alesci et al (2003) showed that Lcarnitine suppressed TNF-α and interleukin-12 release by human primary monocytes when they were stimulated with lipopolysaccharides. It was previously shown that pretreatment with L-carnitine significantly blunted ethanol-induced stimulation of TNF-α release by isolated Kupffer cells (Bykov et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced in the present study, MTX administration resulted in increased serum TNF-α, indicating the role of this cytokine in drug-induced toxicity, while L-carnitine depressed the TNF-α response. Alesci et al (2003) showed that Lcarnitine suppressed TNF-α and interleukin-12 release by human primary monocytes when they were stimulated with lipopolysaccharides. It was previously shown that pretreatment with L-carnitine significantly blunted ethanol-induced stimulation of TNF-α release by isolated Kupffer cells (Bykov et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Alesci et al [26] reported that L -carnitine may act similarly to other tissue/gene-selective glucocorticoid receptor modulators. Pharmacological doses of L -carnitine can activate glucocorticoid receptor ␣ and, by this mechanism, regulate glucocorticoid-responsive genes.…”
Section: Discussionmentioning
confidence: 99%
“…12 Based on our results, we hypothesize as follows: glucocorticoids exert their anti-inflammatory effect by interacting with an intranuclear glucocorticoid receptor α (GR-α). 25,26 Intracellular L-carnitine transported by OCTN1/2, activates allosterically GR-α resulting in its promotion to its intranuclear translocation, following transcriptional stimulation to induce anti-inflammatory responsive genes, such as IκBα or IL-10 in an L-carnitine dose-dependent fashion. [26][27][28] In summary, modulation of carnitine transportation can indirectly affect steroid responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Intracellular L-carnitine transported by OCTN1/2, activates allosterically GR-α resulting in its promotion to its intranuclear translocation, following transcriptional stimulation to induce anti-inflammatory responsive genes, such as IκBα or IL-10 in an L-carnitine dose-dependent fashion. [26][27][28] In summary, modulation of carnitine transportation can indirectly affect steroid responsiveness. Specifically, steroid responsiveness in Japanese patients with Crohn's disease could be tuned by functional and/or transcriptional modulation of OCTN2 by the two-allele haplotype CG.…”
Section: Discussionmentioning
confidence: 99%